Effect of N-2/H-2 plasma on the growth of InN thin films on sapphire by hollow-cathode plasma-assisted atomic layer deposition - ALEVLİ, MUSTAFA (A V S AMER INST PHYSICS, 2020)
In this work, we have studied the influence of N-2/H-2 plasma gas flow rates on the hollow-cathode plasma-assisted atomic layer deposition (HCPA-ALD) growth of indium nitride (InN) films. The influence of N-2/H-2 plasma gas flow rates on crystallinity, lattice distortion, phonon properties, and bandgap was analyzed. We found that the strain can be relieved fully or partially through the incorporation of H-2 in plasma. We present Raman scattering measurements on HCPA-ALD grown InN films. We found that the E-2-high phonon relaxation time increases with decreasing H-2 plasma flow. Atomic force microscopy (AFM) topography measurements revealed high surface roughness for InN films deposited with N-2/H-2. The spectroscopic ellipsometry analysis revealed that InN surface layers are thick and contain large void structures with the incorporation of H-2 in N-2 plasma. Combining the AFM surface morphology analysis with spectroscopic ellipsometry analysis, we propose a possible surface reaction mechanism for hydrogen incorporation on an InN surface. A clear shift of the absorption edge and a decrease in the absorption coefficient were observed when H-2 was introduced into N-2 flow. These results may provide a useful guide for understanding the HCPA-ALD growth mechanism of InN and In-rich nitrides.